Preparation method of nano high-entropy ferrite Fenton-like catalyst, prepared catalyst and application of nano high-entropy ferrite Fenton-like catalyst

By synthesizing nano high entropy ferrite Fenton catalysts in mild conditions, the problems of insufficient catalytic activity and complex process in the prior art are solved, and efficient degradation of emerging organic pollutants is achieved and excellent catalytic activity is achieved. and wide applicability.

CN119425704AActive Publication Date: 2025-02-14JIANGXI SCI & TECH NORMAL UNIV

Patent Information

Application Number
CN202411676450.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-14
Estimated Expiration
2044-11-22

AI Technical Summary

Technical Problem

The existing ferrite Fenton catalysts have insufficient catalytic activity and complex preparation processes, making it difficult to effectively remove emerging organic pollutants.

Method used

Nano-high entropy ferrite Fenton catalyst was synthesized under mild conditions by one-step method, with the chemical formula (MxCoxNi0.2Cu0.2Zn0.2)Fe2O4, and the salt was completely dissolved by stirring in ethanol solution and ultrasonication, and then under an alkaline environment Solvent-thermal reaction was performed and the nanoparticles were finally obtained by washing and drying.

Benefits of technology

The prepared nano-high entropy ferrite Fenton catalyst has regular morphology, high specific surface area and excellent catalytic activity, and can efficiently degrade traditional and emerging organic pollutants, including organic dyes and antibiotics, within a wide pH range. Things.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119425704A_ABST
    Figure CN119425704A_ABST
Patent Text Reader

Abstract

The invention relates to an organic pollutant wastewater treatment technology, in particular to a preparation method and application of a high-entropy ferrite Fenton-like catalyst. The nano high-entropy ferrite is prepared through one-step growth by adopting a low-temperature solvothermal method in a strong alkaline environment, the chemical composition of the nano high-entropy ferrite is (MxCoxNi0. 2Cu0. 2Zn0. 2) Fe2O4, M is Mg and / or Mn, 0 lt, 0, 0, 0, 0, 0, 0, 0, 0, 0, 0, 0, 0, 0, 0, 0, and x is less than or equal to 0.2. According to the invention, the catalytic activity and selectivity design of the Fenton-like catalyst is realized by regulating and controlling the chemical composition of the high-entropy ferrite, and the prepared flaky or regular octahedral high-entropy ferrite has higher catalytic activity than a single phase. The synthesis method of the high-entropy ferrite catalyst provided by the invention has the advantages of low preparation temperature, high universality, simplicity and feasibility, simple equipment and the like, and provides a new way and a new idea for application of the high-entropy ferrite material in the fields of catalysis, energy conversion and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of wastewater treatment, and in particular to a method for preparing nano high-entropy ferrite-like ferrites, a catalyst prepared therefrom and applications thereof. Background Art

[0002] As the emission of emerging organic pollutants such as endocrine disruptors, pharmaceuticals and personal care products (PPCPs) far exceeds the natural degradation capacity, the development of technologies and means to quickly and effectively remove emerging organic pollutants has become a hot topic of global concern. Heterogeneous Fenton-like catalytic degradation technology has high catalytic oxidation energy, a wider pH application window and a faster oxidant activation process. It has great application potential in the construction of catalytic systems for actual PPCPs wastewater treatment and has received extensive academic attention and some commercial applications.

[0003] Ferrites are a type of highly efficient heterogeneous catalytic material with multifunctionality and wide application value due to their low price, flexible composition, adjustable properties, and ability to continuously change the ion charge. After ion replacement or substitution, they can form a continuous solid solution with stable configuration. Spinel ferrites have higher stability and more active sites than single metal catalysts, as well as synergistic effects between metal ions. They gradually dominate heterogeneous Fenton-like systems based on sulfate radicals and hydroxyl radicals. Recently, Professor Qiu Huajun of Harbin Institute of Technology (Shenzhen) has obtained a series of spinel oxides by dealloying multi-component alloys or high-entropy alloys, such as (AlMnCo)3O4 nanosheets, (AlNiCoRuMo)3O4 nanowires, nano-multilevel pores (AlCoFeMoCr)3O4, etc. With their large specific surface area and "cocktail" effect, these materials exhibit excellent oxygen catalytic activity (Adv. Funct. Mater. 31, 2007129 (2021)", "ACS Mater. Lett. 2, 1698-1706 (2020)", "Chem. Mater. 33, 1771-1780 (2021)"), but the above materials are mainly used for the adsorption and degradation of exhaust gases. Although the high entropy design strategy can improve the catalytic activity of materials, there is still room for further improvement, and the traditional methods for preparing high entropy materials include conventional sintering (CS), spark plasma sintering (SPS), flash sintering (FS), etc. However, these preparation methods require higher temperatures, and the preparation temperature exceeds 1000°C, so the equipment and process used for preparation are relatively high.

[0004] CN116282224 discloses a high-entropy spinel catalyst with controllable oxygen vacancy concentration under mild conditions and a preparation method thereof. This catalyst is synthesized by a two-step method of solvothermal treatment combined with annealing treatment at a relatively high temperature, which requires subsequent heat treatment to increase the complexity of the process, and the powder has an irregular shape. At the same time, CN113860911A discloses a preparation method of a high-entropy ferrite porous ceramic material. The high-entropy ferrite powder prepared by this patent needs to be obtained by high-temperature heat treatment. The prepared high-entropy powder belongs to the micron level and has a limited specific surface area, thus limiting the heterogeneous catalytic activity of the catalyst.

[0005] In summary, aiming at the problems of insufficient catalytic activity and complex preparation process of ferrite-based Fenton catalysts in the prior art, the present invention proposes a preparation method of a high-entropy ferrite-based Fenton catalyst. Summary of the Invention

[0006] Aiming at the deficiencies in the prior art, the purpose of the present invention is to provide a preparation method of a nano high-entropy ferrite-based Fenton catalyst. The provided preparation method can synthesize a high-entropy ferrite-based Fenton catalyst by a one-step method under mild conditions, greatly reducing the production cost. The high-entropy ferrite-based Fenton catalyst prepared by this method has a regular morphology and a high specific surface area, and has good catalytic activity. It has good application prospects in the field of heterogeneous activation of persulfate or hydrogen peroxide to treat organic pollutants. Its application range is wide, and it can not only degrade traditional organic dyes, but also has a good degradation effect on emerging organic pollutants such as antibiotics.

[0007] In order to achieve the above invention purpose, the technical solution of the present invention is as follows:

[0008] On the one hand, the present invention provides a preparation method of a high-entropy ferrite-based Fenton catalyst. The chemical formula of the high-entropy ferrite catalyst is (M x Co x Ni 0.2 Cu 0.2 Zn 0.2 )Fe2O4, where M is Mg and / or Mn, 0 < x ≤ 0.2, and the preparation steps include:

[0009] S1. Weigh the salts of M, Co, Ni, Zn, Cu and Fe according to the chemical ratio, then add them to ethanol, stir and ultrasonically treat until the salts are completely dissolved to obtain a mixed solution;

[0010] S2. While dropping an alkaline solution into the mixed solution and stirring, adjust the pH value of the mixed solution to an alkaline environment;

[0011] S3. Place the mixed solution in step S2 in a reaction kettle, and carry out a solvothermal reaction at 140 - 220 °C for 18 - 36 h, and then obtain a precipitate;

[0012] S4. Wash and dry the precipitate to obtain a nano high-entropy ferrite Fenton catalyst.

[0013] Furthermore, the high entropy ferrite Fenton catalyst is in the form of a regular octahedron and / or flake, with a particle size of 20 to 50 nm and a specific surface area of ​​50 to 160 m 2 / g.

[0014] Due to its regular shape, it has good dispersibility in wastewater and has a better catalytic effect. Due to its nano-size effect and high specific surface area, it has higher catalytic activity than micron-sized Fenton-like catalytic materials.

[0015] In the specific surface area of ​​50~160m 2 / g range, the high entropy ferrite Fenton catalyst can better form a complex with hydrogen peroxide or persulfate, has better adsorption to the reaction substrate, can efficiently realize electron transfer under mild conditions, and improve the catalytic degradation efficiency.

[0016] Furthermore, the salt in step S1 may be nitrate or sulfate, and the molar concentration thereof is 0.01 to 0.1 mol / L.

[0017] Furthermore, the alkaline solution in step S2 is at least one of ammonia water, sodium hydroxide or potassium hydroxide solution, with a concentration of 4.0 to 6.0 mol / L, and the hydroxide ion concentration in the mixed solution is adjusted to 0.40 to 0.65 mol / L.

[0018] Furthermore, in step S4, the precipitate is washed with distilled water and ethanol for 3 to 6 times respectively, and then dried in an oven at 50 to 70° C. for 20 to 48 hours.

[0019] On the other hand, the present invention provides a nano high-entropy ferrite Fenton catalyst prepared by the above preparation method.

[0020] The nano high-entropy ferrite Fenton catalyst obtained by the above method adopts a ferrite solid solution compound composed of more than 6 elements, has a high entropy value, has high thermodynamic stability, and the atoms interact with each other to produce lattice distortion. It can simultaneously couple the redox processes of multiple variable-valence metal ions, and can better achieve the reduction of high-valence ions in the process of activating hydrogen peroxide, peroxydisulfate (PDS) and peroxymonosulfate (PMS), showing excellent catalytic activity and stability; compared with low-entropy catalysts such as ZnFe2O4, CoFe2O4, and NiFe2O4, it shows better catalytic degradation effect and efficiency in catalytic degradation of organic pollutants.

[0021] On the other hand, the present invention provides an application of a nano high entropy ferrite Fenton catalyst prepared by the above preparation method in degrading organic pollutants in wastewater.

[0022] Furthermore, the pH value of the wastewater solution is 4 to 11. Compared with the traditional Fenton catalyst, which has certain requirements on the pH value of wastewater when using hydrogen peroxide to degrade organic matter, it can only have good degradation activity in a narrow pH range. The high entropy ferrite Fenton catalyst of the present invention can maintain excellent catalytic activity in a liquid phase environment with a pH value of 4 to 11, and has a wider range of application.

[0023] Furthermore, the organic pollutants include at least one of organic dyes, organophosphorus pesticides or antibiotic pollutants. The nano high entropy ferrite Fenton catalyst can not only catalyze and degrade traditional organic pollutants, but also catalyze and degrade emerging antibiotic pollutants, and has a wide range of applications.

[0024] Furthermore, the organic dye includes at least one of methyl orange, rhodamine B, and methylene blue; the antibiotic pollutants include at least one of tetracycline hydrochloride or sulfamethoxazole (SMX) or fluoroquinolone antibiotics.

[0025] Compared with the prior art, the present invention has the following technical effects:

[0026] (1) The nano high entropy ferrite (M) provided by the present invention x Co x Ni 0.2 Cu 0.2 Zn 0.2 )The raw materials required for the preparation of Fe2O4-type Fenton catalysts are cheap, the process control is convenient, and no high-temperature heat treatment is required. Nano-high-entropy ferrite particles with regular shape, high crystallinity, high specific surface area and high catalytic activity can be prepared under mild conditions without the addition of surfactants. It has the advantages of low production cost, high universality, simplicity and ease of operation, and simple equipment. It provides a new way and new ideas for the application of high-entropy ferrite materials in catalysis, energy conversion and other fields.

[0027] (2) The nano high entropy ferrite (M) provided by the present invention x Co x Ni 0.2 Cu 0.2 Zn 0.2)Fe2O4 Fenton catalyst has great application value in activating hydrogen peroxide and persulfate to degrade typical organic pollutants and emerging organic pollutants, and has excellent catalytic activity and stability; the degradation rate of traditional organic pollutants such as methyl orange, rhodamine B, and methylene blue is more than 87%, and for methyl orange it is even more than 93%. For emerging organic pollutants such as tetracycline hydrochloride or sulfamethoxazole (SMX) or fluoroquinolone antibiotics, it generally reaches more than 86%, and the degradation rate of tetracycline hydrochloride can even reach more than 95%.

[0028] (3) The high-entropy ferrite Fenton catalyst provided by the present invention has a high specific surface area, can form a complex with hydrogen peroxide or persulfate, has good adsorption capacity for reaction substrates, and can efficiently realize electron transfer under mild conditions, showing excellent degradation effect on emerging organic pollutants.

[0029] (4) The nano high-entropy ferrite Fenton catalyst provided by the present invention is applicable to the pH value range of the liquid phase environment of 4 to 11, has a wide application range, and is easy to disperse evenly in the solution. It has a stronger catalytic degradation effect and efficiency in degrading organic pollutants than low-entropy catalysts composed of a single phase, such as ZnFe2O4, CoFe2O4, and NiFe2O4. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 The high entropy (Mg) 0.2 Co 0.2 Ni 0.2 Zn 0.2 Cu 0.2 )TEM image of Fe2O4.

[0031] Figure 2 The high entropy (Mg) 0.2 Co 0.2 Ni 0.2 Zn 0.2 Cu 0.2 )XRD pattern of Fe2O4.

[0032] Figure 3 The high entropy (Mg) 0.2 Co 0.2 Ni 0.2 Zn 0.2 Cu 0.2 )Particle size distribution of Fe2O4.

[0033] Figure 4 The high entropy (Mn 0.2 Co0.2 Ni 0.2 Zn 0.2 Cu 0.2 )TEM image of Fe2O4.

[0034] Figure 5 High Entropy (Mg 0.2 Co 0.2 Ni 0.2 Zn 0.2 Cu 0.2 ) Kinetic process of degradation of tetracycline hydrochloride (TCH) by Fe2O4 activation of hydrogen peroxide (H2O2), peroxydisulfate (PDS) and peroxymonosulfate (PMS).

[0035] Figure 6 High entropy (Mg) at different initial pH values 0.2 Co 0.2 Ni 0.2 Zn 0.2 Cu 0.2 ) Kinetic process of degradation of tetracycline hydrochloride (TCH) by Fe2O4-activated peroxymonosulfate (PMS).

[0036] Figure 7 Nano high entropy (Mn 0.2 Co 0.2 Ni 0.2 Zn 0.2 Cu 0.2 )Fe2O4-type Fenton catalyst. DETAILED DESCRIPTION

[0037] The following non-limiting examples can enable those skilled in the art to more fully understand the present invention, but do not limit the present invention in any way. The following content is merely an exemplary description of the scope of protection claimed in this application. Those skilled in the art can make various changes and modifications to the invention of this application based on the disclosed content, and they should also fall within the scope of protection claimed in this application. The term "about" means within 10% of a certain value, for example, about 20 nanometers, i.e., 20±2 nanometers.

[0038] The present invention is further described below by way of specific examples. Unless otherwise specified, the various chemical reagents used in the examples of the present invention are obtained through conventional commercial channels.

[0039] Example 1 High Entropy (Mg 0.2 Co 0.2 Ni 0.2 Zn 0.2 Cu 0.2 )Preparation of Fe2O4

[0040] According to (Mg 0.2 Co0.2 Ni 0.2 Zn 0.2 Cu 0.2 )Fe2O4 is prepared in a stoichiometric ratio, that is, magnesium nitrate, cobalt nitrate, nickel nitrate, zinc nitrate, copper nitrate and iron nitrate are weighed in sequence according to a metal molar ratio of 0.2:0.2:0.2:0.2:0.2, and the nitrates are added to the ethanol solution in sequence, stirred until completely dissolved, and ultrasonicated for 20 minutes; then the pH of the mixed solution is adjusted with a sodium hydroxide solution, and the concentration of hydroxide ions is adjusted to 0.5 mol / L; the mixture is reacted at 180°C for 20 hours, and a solvent thermal reaction is performed to obtain a heat-treated mixed solution. After the heat-treated mixed solution obtained in the above steps is cooled, the product is centrifuged and washed, and the product is dried in an oven at 70°C. Figure 1 For the preparation of high entropy (Mg 0.2 Co 0.2 Ni 0.2 Zn 0.2 Cu 0.2 )TEM image of Fe2O4. Figure 2 For the preparation of high entropy (Mg 0.2 Co 0.2 Ni 0.2 Zn 0.2 Cu 0.2 )XRD pattern of Fe2O4. Figure 3 For the preparation of high entropy (Mg 0.2 Co 0.2 Ni 0.2 Zn 0.2 Cu 0.2 )Particle size distribution of Fe2O4.

[0041] Example 2 High Entropy (Mn 0.2 Co 0.2 Ni 0.2 Zn 0.2 Cu 0.2 )Preparation of Fe2O4

[0042] According to (Mn 0.2 Co 0.2 Ni 0.2 Zn 0.2 Cu 0.2)Fe2O4 is prepared in a stoichiometric ratio, that is, manganese nitrate, cobalt nitrate, nickel nitrate, zinc nitrate, copper nitrate and iron nitrate are weighed in sequence according to a metal molar ratio of 0.2:0.2:0.2:0.2:0.2, and the nitrates are added to the ethanol solution in sequence, stirred until completely dissolved, and ultrasonicated for 20 minutes; then the pH of the mixed solution is adjusted with a sodium hydroxide solution, and the concentration of hydroxide ions is controlled at 0.65 mol / L; the mixture is reacted at 200°C for 30 hours, and a solvent thermal reaction is performed to obtain a heat-treated mixed solution. After the heat-treated mixed solution obtained in the above steps is cooled, the product is centrifuged and washed, and the product is dried in an oven at 70°C. Figure 4 For the prepared high entropy (Mn 0.2 Co 0.2 Ni 0.2 Zn 0.2 Cu 0.2 )TEM image of Fe2O4.

[0043] Example 3 Preparation of high entropy (Mn) under different strong alkaline environments 0.2 Co 0.2 Ni 0.2 Zn 0.2 Cu 0.2 )Fe2O4

[0044] According to (Mn 0.2 Co 0.2 Ni 0.2 Zn 0.2 Cu 0.2 )Fe2O4 is prepared in a stoichiometric ratio, i.e., manganese nitrate, cobalt nitrate, nickel nitrate, zinc nitrate, copper nitrate and iron nitrate are weighed in sequence according to a metal molar ratio of 0.2:0.2:0.2:0.2:0.2:2, and the nitrates are added to the ethanol solution in sequence, stirred until completely dissolved, and ultrasonicated for 20 minutes; then, the pH of the mixture is adjusted with a sodium hydroxide solution, and the concentration of hydroxide ions is controlled between 0.41 and 0.50 mol / L; then, the mixture is reacted at 180°C for 20 hours to perform a solvent thermal reaction to obtain a heat-treated mixture. After the heat-treated mixture obtained in the above steps is cooled, the product is centrifuged and washed, and the product is dried in an oven at 70°C to obtain a series of powders. The results are as follows Figure 7 As shown, from Figure 7 It can be seen that when the hydroxide ion concentration is greater than or equal to 0.50 mol / L, the one-step solvothermal method can prepare single-phase nano high entropy (Mn 0.2 Co 0.2 Ni 0.2 Zn 0.2 Cu 0.2 )Fe2O4.

[0045] Example 4 Preparation of high entropy (Mn) in ultra-high alkaline environment 0.2 Co0.2 Ni 0.2 Zn 0.2 Cu 0.2 )Fe2O4

[0046] According to (Mn 0.2 Co 0.2 Ni 0.2 Zn 0.2 Cu 0.2 )Fe2O4 is prepared in a stoichiometric ratio, i.e., manganese sulfate, cobalt sulfate, nickel sulfate, zinc sulfate, copper sulfate and iron sulfate are weighed in sequence according to a metal molar ratio of 0.2:0.2:0.2:0.2:0.2:2, and the sulfates are added to the ethanol solution in sequence, stirred until completely dissolved, and ultrasonicated for 20 minutes; then, the pH of the mixture is adjusted with a sodium hydroxide solution, and the concentration of hydroxide ions is controlled between 0.62 mol / L; then, the mixture is reacted at 180°C for 20 hours to perform a solvent thermal reaction to obtain a heat-treated mixture. After the heat-treated mixture obtained in the above steps is cooled, the product is centrifuged and washed, and the product is dried in an oven at 70°C to obtain a series of powders. The results are as follows Figure 7 As shown, from Figure 7 It can be seen that when the hydroxide ion concentration is 0.62 mol / L, the one-step solvothermal method can prepare a single-phase nano high entropy (Mn 0.2 Co 0.2 Ni 0.2 Zn 0.2 Cu 0.2 )Fe2O4.

[0047] Comparative Example 1 Preparation of a single component ZnFe2O4

[0048] The ingredients are prepared according to the stoichiometric ratio of ZnFe2O4, zinc nitrate and iron nitrate are weighed and added to the ethanol solution in sequence, magnetically stirred and rotated until completely dissolved, and ultrasonicated for 20 minutes; then the pH environment of the mixed solution is adjusted with sodium hydroxide solution, and the concentration of hydroxide ions is controlled at 0.50 mol / L; the mixture is reacted at 180°C for 20 hours, and a solvent thermal reaction is performed to obtain a heat-treated mixed solution. After the heat-treated mixed solution obtained in the above steps is cooled, the product is centrifuged and washed, and the product is dried in an oven at 70°C.

[0049] Comparative Example 2 Preparation of Single Component CoFe2O4

[0050] The ingredients are prepared according to the stoichiometric ratio of ZnFe2O4, cobalt nitrate and iron nitrate are weighed and added to the ethanol solution in sequence, magnetically stirred and rotated until completely dissolved, and ultrasonicated for 20 minutes; then the pH environment of the mixed solution is adjusted with sodium hydroxide solution, and the concentration of hydroxide ions is controlled at 0.50 mol / L; the mixture is reacted at 180°C for 20 hours, and a solvent thermal reaction is performed to obtain a heat-treated mixed solution. After the heat-treated mixed solution obtained in the above steps is cooled, the product is centrifuged and washed, and the product is dried in an oven at 70°C.

[0051] Comparative Example 3 Preparation of Single Component NiFe2O4

[0052] The ingredients are prepared according to the stoichiometric ratio of NiFe2O4, nickel sulfate and ferric nitrate are weighed and added to the ethanol solution in sequence, magnetically stirred and rotated until completely dissolved, and ultrasonicated for 20 minutes; then the pH environment of the mixed solution is adjusted with sodium hydroxide solution, and the concentration of hydroxide ions is controlled at 0.60 mol / L; the mixture is reacted at 220°C for 36 hours, and a solvent thermal reaction is performed to obtain a heat-treated mixed solution. After the heat-treated mixed solution obtained in the above steps is cooled, the product is centrifuged and washed, and the product is dried in an oven at 70°C.

[0053] Test Example 1: Comparison of performance in degradation of typical organic pollutants

[0054] 1. Test materials: Nano high entropy ferrite Fenton catalysts prepared in Examples 1-4 and single component ZnFe2O4, CoFe2O4 and NiFe2O4 Fenton catalysts prepared in Comparative Examples 1-3.

[0055] 2. Test method: Take typical other organic pollutants methyl orange, rhodamine B, methylene blue and methyl parathion as the target pollutants of the Fenton-like catalytic reaction, and carry out the Fenton-like catalytic reaction test to characterize the performance difference between the nano high entropy ferrite Fenton-like catalyst prepared in Example 1-4 and the single component ZnFe2O4, CoFe2O4 and NiFe2O4 Fenton-like catalyst prepared in Comparative Example 1-3. The initial concentration of the typical organic pollutants used is 100 mg / L, the addition amount of the test sample is 1 g / L, and the concentration of peroxymonosulfate (PMS) is 150 mM. Before the Fenton-like degradation reaction, take 80 mL of the typical organic pollutant solution, add the test sample to the typical organic pollutant solution respectively, stir in the dark room for 60 min to reach the adsorption-desorption equilibrium, and then carry out the Fenton-like catalytic degradation test. After the catalytic degradation reaction for 90 min, centrifuge to separate the catalyst remaining in the solution. Then use a UV-visible spectrophotometer to measure the absorbance of the supernatant. The change in the absorbance of the solution is measured to analyze the concentration change of organic pollutants in the solution, and then characterize the catalytic activity of the Fenton-like catalyst.

[0056] 3. Test results: The test results are shown in Table 1.

[0057] As shown in Table 1, the nano high entropy ferrite Fenton-like catalysts prepared in Examples 1-4 have a Fenton-like catalytic degradation efficiency of more than 87% for methyl orange, rhodamine B, methylene blue and methyl parathion, and have a good catalytic degradation effect. 0.2 Co 0.2 Ni 0.2 Zn 0.2 Cu 0.2 )Fe2O4-type Fenton catalytic degradation has the highest comprehensive efficiency. In comparison, the overall catalytic degradation efficiency of the single-component ZnFe2O4, CoFe2O4 and NiFe2O4-type Fenton catalysts prepared in Comparative Examples 1-3 is less than 81%, and the catalytic degradation efficiency is low. The results show that the nano high-entropy ferrite-type Fenton catalyst provided by the present invention has an obvious Fenton-like catalytic degradation effect on typical organic pollutants such as methyl orange, rhodamine B, methylene blue and methyl parathion, and has excellent comprehensive catalytic degradation activity.

[0058] Table 1 Test results of degradation of typical organic pollutants by Fenton-type reaction

[0059]

[0060] Test Example 2: Experimental Data Description

[0061] Figure 1 The high entropy (Mg) prepared in Example 1 0.2 Co 0.2 Ni 0.2 Zn 0.2 Cu 0.2 )TEM photo of Fe2O4. The synthesized high-entropy powder has a regular octahedral shape and is in the nanometer size range.

[0062] Figure 2 The nano high entropy (Mg 0.2 Co 0.2 Ni 0.2 Zn 0.2 Cu 0.2 )Fe2O4, the diffraction peak of the synthesized powder is located between the five single components, indicating that the five elements are well dissolved in the lattice, and the high configuration entropy formed by the equimolar ratio promotes the compatibility between the elements and the formation of solid solution. No other impurity peaks and second phases appear, indicating that a high entropy material with a single phase (Mg) was successfully synthesized. 0.2 Co 0.2 Ni 0.2 Zn 0.2 Cu 0.2 )Fe2O4.

[0063] Figure 3 The nano high entropy (Mg 0.2 Co 0.2 Ni 0.2 Zn 0.2 Cu 0.2 )Particle size distribution of Fe2O4, the average grain size is 20.4nm.

[0064] Figure 4 is the (Mn 0.2 Co 0.2 Ni 0.2 Zn 0.2 Cu 0.2 )Fe2O4 was photographed by TEM, and the synthesized high entropy powder was in a regular flake shape and was in the nanometer size range.

[0065] Figure 5 The nano high entropy (Mg 0.2 Co 0.2 Ni 0.2 Zn 0.2 Cu 0.2 )Fe2O4 activated hydrogen peroxide (H2O2), peroxydisulfate (PDS) and peroxymonosulfate (PMS) to degrade tetracycline hydrochloride (TCH) kinetics. Figure 5 It can be seen that high entropy (Mg 0.2 Co 0.2 Ni 0.2 Zn 0.2 Cu 0.2 )Fe2O4 has good adsorption properties for tetracycline hydrochloride, and has obvious catalytic degradation effects when activating hydrogen peroxide, peroxydisulfate (PDS) and peroxymonosulfate (PMS). Among them, the activated peroxymonosulfate has the best effect, and the complete degradation of high-concentration tetracycline hydrochloride can be achieved in about 90 minutes of catalytic degradation.

[0066] The specific implementation process of the Fenton-like catalytic reaction is as follows: 3 cups of 80 mL tetracycline hydrochloride solution (TCH, concentration of 100 mg / L) are respectively placed in the reactor, and then hydrogen peroxide (H2O2) with a concentration of 150 mM, peroxydisulfate (PDS) with a concentration of 150 mM, peroxymonosulfate (PMS) with a concentration of 150 mM, and high entropy (Mg 0.2 Co 0.2 Ni 0.2 Zn 0.2 Cu 0.2 )Fe2O4 powder concentration 1.0g / L. The removal rate (Rev(%)) of the simulated target pollutant tetracycline hydrochloride can be calculated using the following formula:

[0067]

[0068] Among them C t represents the concentration of organic pollutants in the filtrate at a certain moment; C0 represents the initial concentration of organic pollutants; A t It represents the absorbance at the maximum absorption wavelength of organic pollutants in the filtrate at a certain moment (the characteristic absorption peak of tetracycline hydrochloride is 357nm); A0 represents the absorbance at the maximum absorption wavelength of the initial organic pollutants.

[0069] Figure 6 The nano high entropy (Mn) prepared in Example 3 0.2 Co 0.2 Ni 0.2 Zn 0.2 Cu 0.2 )Fe2O4 was used to verify the degradation of tetracycline hydrochloride under different initial pH values. The results showed that nano high entropy (Mn 0.2 Co 0.2 Ni 0.2 Zn 0.2 Cu 0.2 )Fe2O4 is applicable in a wide pH environment and has a very good activation effect on peroxymonosulfate. The reaction system has an excellent effect of degrading organic pollutants.

[0070] The specific reaction process is as follows: several 80 mL portions of tetracycline hydrochloride solution (TCH, concentration of 100 mg / L) are measured, and then the initial pH of the solution is adjusted to the target value (3, 5, 7, 9, 11 and 12 and the control group without adding acid or alkali pH = 5.0) with sodium hydroxide solution and hydrochloric acid. The optimal addition amount of hydrogen peroxide concentration and catalyst concentration is: the concentration of peroxymonosulfate (PMS) is 150 mM, and the concentration of nano high entropy (Mn 0.2 Co 0.2 Ni 0.2 Zn 0.2 Cu 0.2 )Fe2O4 powder concentration 1g / L. The operation steps are as follows: First, nano high entropy (Mn 0.2 Co 0.2 Ni 0.2 Zn 0.2 Cu 0.2 )Fe2O4 is added to the tetracycline hydrochloride solution, and the pH is adjusted after the adsorption-desorption equilibrium is reached. After the absorbance is stabilized again, hydrogen peroxide is added to react. The removal rate (Rev (%)) of the simulated target pollutant tetracycline hydrochloride can be calculated using the following formula:

[0071]

[0072] Among them C trepresents the concentration of organic pollutants in the filtrate at a certain moment; C0 represents the initial concentration of organic pollutants; A t It represents the absorbance at the maximum absorption wavelength of organic pollutants in the filtrate at a certain moment (the characteristic absorption peak of tetracycline hydrochloride is 357nm); A0 represents the absorbance at the maximum absorption wavelength of the initial organic pollutants.

[0073] Test Example 3: Test on the catalytic degradation performance of Fenton-like catalysts on antibiotic organic pollutants

[0074] 1. Test materials: Nano high entropy ferrite Fenton catalysts prepared in Examples 1-4 and single component ZnFe2O4, CoFe2O4 and NiFe2O4 Fenton catalysts prepared in Comparative Examples 1-3.

[0075] 2. Test method: The antibiotic organic pollutants tetracycline hydrochloride, sulfamethoxazole (SMX), and fluoroquinolone antibiotics were used as the target pollutants of the Fenton-like catalytic reaction, and the Fenton-like catalytic reaction test was carried out to characterize the performance difference between the nano high entropy ferrite Fenton-like catalysts prepared in Examples 1-4 and the single component ZnFe2O4, CoFe2O4, and NiFe2O4 Fenton-like catalysts prepared in Comparative Examples 1-3. The initial concentration of the typical organic pollutants used was 150 mg / L, the addition amount of the test sample was 1 g / L, and the concentration of hydrogen peroxide (H2O2) was 150 mM. Before the Fenton-like degradation reaction, 80 mL of the antibiotic organic pollutant solution was taken, and the test samples were added to the antibiotic organic pollutant solution respectively, and the adsorption-desorption equilibrium was reached under stirring in a dark room for 90 min, and then the Fenton-like catalytic degradation test was carried out. After the catalytic degradation reaction for 120 min, centrifugation was performed to separate the catalyst remaining in the solution. The absorbance of the supernatant was then measured using a UV-visible spectrophotometer. The change in the absorbance of the solution is measured to analyze the concentration change of antibiotic organic pollutants in the solution, and then characterize the catalytic activity of the Fenton-like catalyst.

[0076] 3. Test results: The test results are shown in Table 2.

[0077] As shown in Table 2, the nano high entropy ferrite Fenton-like catalysts prepared in Examples 1-4 have a Fenton-like catalytic degradation efficiency of more than 86.3% for tetracycline hydrochloride, sulfamethoxazole (SMX), and fluoroquinolone antibiotics, and have a good catalytic degradation effect. 0.2 Co 0.2 Ni 0.2 Zn 0.2 Cu 0.2)Fe2O4-type Fenton catalytic degradation of antibiotic pollutants has the highest comprehensive efficiency. In comparison, the overall catalytic degradation efficiency of the single-component ZnFe2O4, CoFe2O4 and NiFe2O4-type Fenton catalysts prepared in Comparative Examples 1-3 is less than 82.7%, and the catalytic degradation efficiency is relatively low. The results show that the nano high-entropy ferrite-type Fenton catalyst provided by the present invention has an obvious Fenton-like catalytic degradation effect on emerging organic pollutants such as tetracycline hydrochloride, sulfamethoxazole (SMX), and fluoroquinolone antibiotics, and has excellent comprehensive catalytic degradation activity.

[0078] Table 2 Test results of catalytic degradation performance of Fenton-type catalysts on antibiotic organic pollutants

[0079]

[0080] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a nano high-entropy ferrite catalyst, the chemical formula of the high-entropy ferrite catalyst being (M x Co x Ni 0.2 Cu 0.2 Zn 0.2 )Fe2O4, where M is Mg and / or Mn, 0 < x ≤ 0.2, characterized in that, The method comprises the following preparation steps: S1. Weigh salts of M, Co, Ni, Zn, Cu and Fe according to chemical proportions, add them to ethanol, stir and ultrasonicate until the salts are completely dissolved to obtain a mixed solution; S2, adding an alkaline solution dropwise to the mixed solution while stirring, and adjusting the pH value of the mixed solution to an alkaline environment; S3, placing the mixed solution in step S2 in a reaction kettle, and performing a solvothermal reaction at 140-220° C., keeping the temperature for 18-36 hours, and then obtaining a precipitate; S4. Wash and dry the precipitate to obtain a nano high-entropy ferrite Fenton catalyst.

2. The method for preparing a nano high entropy ferrite catalyst according to claim 1, characterized in that: The specific surface area of ​​the nano high entropy ferrite Fenton catalyst is 50 to 160 m 2 / g, the particle shape of the nano high entropy ferrite Fenton catalyst is at least one of a regular octahedron or a flake, and the average particle size is 20 to 50 nm.

3. The method for preparing a nano high entropy ferrite catalyst according to claim 1, characterized in that: In step S1, the salt is nitrate and / or sulfate, and its molar concentration after dissolution is 0.01-0.1 mol / L.

4. The method for preparing a nano high entropy ferrite catalyst according to claim 1, characterized in that: The alkaline solution in step S2 is at least one of ammonia water, sodium hydroxide or potassium hydroxide solution, with a concentration of 4.0 to 6.0 mol / L, and the hydroxide ion concentration in the mixed solution is adjusted to 0.40 to 0.65 mol / L.

5. The method for preparing a nano high entropy ferrite catalyst according to claim 1, characterized in that: In step S4, the precipitate is washed with distilled water and ethanol for 3 to 6 times respectively, and then dried in an oven at 50 to 70° C. for 20 to 48 hours.

6. A nano high-entropy ferrite Fenton catalyst prepared by the method described in any one of claims 1 to 5.

7. Use of the nano high entropy ferrite Fenton catalyst according to claim 6 in degrading organic pollutants in wastewater.

8. The use according to claim 6, characterized in that The pH value of the wastewater solution environment is 4-11.

9. The use according to claim 6, wherein the organic pollutants include at least one of organic dyes, organophosphorus pesticides or antibiotic pollutants.

10. The use according to claim 9, wherein the organic dye comprises at least one of methyl orange, rhodamine B, and methylene blue; and the antibiotic pollutant comprises at least one of tetracycline, sulfamethoxazole, or fluoroquinolone antibiotics.

Citation Information

Patent Citations

  • Cu1-XCoXFe2O4 Fenton-like catalyst and preparation method and application thereof

    CN110124671A

  • High-entropy ferrite porous ceramic material as well as preparation method and application thereof

    CN113860911A

  • Mixed ferrite nanoparticles and uses thereof

    WO2024031180A1

Cited By

  • Fenton-like composite catalyst as well as preparation method and application thereof

    CN122352269A